DEMONSTRATION OF SWITCHED CV-QDK NETWORK - Korotkova Larisa Aleksandrovna; Yuldasheva Diyora Ravshanovna (Journals Park Publishing, 2023)
A quantum channel is a physical media able to carry quantum signals. Quantum key distribution (QKD) requires direct quantum channels between every pair of prepare and measure modules. This requirement heavily compromises the scalability of networks of directly connected QKD modules. A way to avoid this problem is to introduce switches that can dynamically reconfigure the set of connections. The reconfiguration of a quantum channel implies that the modules using it can adapt to the new channel and peer.
Keywords: QKD, quantum channel, SNR, IP.